2017
DOI: 10.1016/j.cell.2017.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Classifying Drosophila Olfactory Projection Neuron Subtypes by Single-Cell RNA Sequencing

Abstract: Summary The definition of neuronal type and how this relates to the transcriptome are open questions. Drosophila olfactory projection neurons (PNs) are among the best-characterized neuronal types: different PN classes target dendrites to distinct olfactory glomeruli, while PNs of the same class exhibit indistinguishable anatomical and physiological properties. Using single-cell RNA-sequencing, we comprehensively characterized the transcriptomes of most PN classes and unequivocally mapped transcriptomes to spec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
189
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 245 publications
(212 citation statements)
references
References 56 publications
11
189
0
Order By: Relevance
“…Although future experiments are needed to compare cortical microcircuit architecture in specific cortical areas, our findings suggest that in the developing human cortex, topographically distinct minicolumns consist of different classes of excitatory neurons. Importantly, similar area-specific neuronal signatures have been reported in the adult mouse brain (20), indicating that the topographic variation that we described reflects differences in neuronal identities, rather than transient developmental variation (21).…”
Section: Excitatory Neurons and Connectivitysupporting
confidence: 83%
“…Although future experiments are needed to compare cortical microcircuit architecture in specific cortical areas, our findings suggest that in the developing human cortex, topographically distinct minicolumns consist of different classes of excitatory neurons. Importantly, similar area-specific neuronal signatures have been reported in the adult mouse brain (20), indicating that the topographic variation that we described reflects differences in neuronal identities, rather than transient developmental variation (21).…”
Section: Excitatory Neurons and Connectivitysupporting
confidence: 83%
“…We selected a panel of 258 genes for MERFISH imaging (Figure 1a) by combining three distinct approaches: (i) 62 canonical marker genes for major neuronal and non-neuronal cell types in the cortex were selected based on prior knowledge; (ii) 168 genes were selected based on pair-wise differential gene expression analysis on the neuronal clusters identified by a concurrent singlecell / single-nucleus RNA-sequencing (sc/snRNA-seq) study reported in a companion BICCN paper 38 ; (iii) a set of genes (50 for glutamatergic and 50 for GABAergic neuronal clusters) were selected which contained the highest mutual information 39,40 among the clusters identified by sc/snRNA-seq. The overlapping gene lists generated by these three approaches were combined to form a panel of 258 genes total, in which 242 were imaged using MERFISH, and the remaining 16 genes, which were either relatively short or highly expressed, were measured in eight sequential rounds of a two-color FISH following MERFISH.…”
Section: Single-cell Gene Expression Profiling and Cell Type Identifimentioning
confidence: 99%
“…To discriminate different neuronal types, we took two approaches to select genes. In the first approach, we selected a panel of most informative genes using mutual information analysis as reported previously 39 . Briefly, we used an information theory quantity known as mutual information 40 to determine the relative amount of information each gene carries in defining the sc/snRNA-seq clusters.…”
Section: Gene Selection For Merfishmentioning
confidence: 99%
“…Recent progress in single-cell transcriptome sequencing has also facilitated the creation of databases that allow mining of gene expression in the brain (http://scope.aertslab.org) and gut (https://www.flyrnai.org/scRNA/) at the cellular level [117][118][119][120]. In some cases the name of the precursor is used (when the peptides derived have multiple names and/or when multiple peptides derived from the same precursor are listed).…”
Section: Drosophila 10mentioning
confidence: 99%